Implementasi Tayangan Youtube Riko The Series Terhadap Pengembangan Nilai Agama Dan Moral Pada Anak Usia Dini - Stiani , Dewi; Iskandar , Rhoma; Anggraeni , Rita Intan (CV. ITTC INDONESIA, 2024)
Dewi Stiani. The Implementation of YouTube Show Riko The Series on the Development of Religious and Moral Values in Early Childhood. 2024 Thesis. Bekasi. Faculty of Education Sciences, Early Childhood Teacher Education, Universitas Panca Sakti Bekasi. This study aims to examine the implementation of the YouTube Show Riko The Series on the development of religious and moral values. It uses an instrument for assessing the development of religious and moral values in 5-6 year old children. The research method employed is descriptive with a qualitative approach. The subjects of this research are children aged 5-6 years in class B at TKQ Daarul Musthofa. Data collection techniques involve observation and documentation, with qualitative data analysis conducted through several activites data reduction, data presentation, and data verification or conclusion. The research findings indicate thar the development of religious and moral values in children (Aged 5-6 years) hes improved after watching the YouTube show riko The Series. This study underscores the significance of early childhood education, particualarly concerning the development of religious and moral values in young children.